Nitrogen‐Superdoped 3D Graphene Networks for High‐Performance Supercapacitors. Issue 36 (24th July 2017) - Zhang, Weili; Xu, Chuan; Ma, Chaoqun; Li, Guoxian; Wang, Yuzuo; Zhang, Kaiyu; Li, Feng; Liu, Chang; Cheng, Hui‐Ming; Du, Youwei; Tang, Nujiang; Ren, Wencai
Abstract : An N‐superdoped 3D graphene network structure with an N‐doping level up to 15.8 at% for high‐performance supercapacitor is designed and synthesized, in which the graphene foam with high conductivity acts as skeleton and nested with N‐superdoped reduced graphene oxide arogels. This material shows a highly conductive interconnected 3D porous structure (3.33 S cm −1 ), large surface area (583 m 2 g −1 ), low internal resistance (0.4 Ω), good wettability, and a great number of active sites. Because of the multiple synergistic effects of these features, the supercapacitors based on this material show a remarkably excellent electrochemical behavior with a high specific capacitance (of up to 380, 332, and 245 F g −1 in alkaline, acidic, and neutral electrolytes measured in three‐electrode configuration, respectively, 297 F g −1 in alkaline electrolytes measured in two‐electrode configuration), good rate capability, excellent cycling stability (93.5% retention after 4600 cycles), and low internal resistance (0.4 Ω), resulting in high power density with proper high energy density. Abstract : A N‐superdoped 3D graphene network structure is synthesized to achieve a highly conductive interconnected 3D porous structure and high N‐doping level simultaneously. The supercapacitors based on this material show a remarkably high capacity, good rate capability, and excellent cycling stability.